Wheat blast and phenylalanine ammonia-lyase gene expression in young plants - Cruz, Maria Fernanda Antunes da; Pinheiro, Franciele Cabral; Liska, Gilberto Rodrigues (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to quantify the expression of the PAL gene, designed from TraesCS1D03G0078900 (Chr1D), in young plants of the BRS Louro wheat cultivar challenged with Pyricularia oryzae. The first symptoms of blast were observed at 48 hours after inoculation (HAI). At 120 HAI, severity was 90%. The expression of the PAL gene was upregulated in infected plants at 48, 72, 96, and 120 HAI. After 48 HAI, there was a reduction in gene expression, which continued until 120 HAI. The PAL gene located on chromosome 1D is upregulated in BRS Louro cultivar; however, it is not efficient in restricting the colonization by P. oryzae.